Pengaruh Customer Relationship Management dan Kualitas Pelayanan terhadap Loyalitas Konsumen: Studi pada Konsumen Toko Eka Walet di Kota Jambi - Johanes Alianto; Budi Santosa Kramadibrata (CV. Ulil Albab Corp, 2022)
The increasing business competition in every business sector is a problem for entrepreneurs and prospective entrepreneurs. In order to get consumers and retain consumers even though there are many offers from competitors, it is important for entrepreneurs to be able to maintain a sense of loyalty in consumers. This study aims to determine whether Customer Relationship Management and service quality affect consumer loyalty to consumers of Eka Walet Stores in Jambi City. This study uses quantitative research using primary data with a sample size of 80 respondents. The data was collected using a questionnaire method with a Likert scale. Instrument testing uses validity test, reliability test and classical assumption test with a significance level of 5%. The data analysis used includes descriptive and correlation analysis. The data analysis method uses multiple linear regression models with hypothesis testing using the R Square test, t test and f test. The results of the study indicate that Customer Relationship Management has a positive and significant effect on customer loyalty at Eka Walet Shop as evidenced by the t value (2.851) > t table (1.991). Service quality also shows that it has a positive and significant effect on customer loyalty at Eka Walet Shop as evidenced by the t value (5.809) > t table (1.991). Customer Relationship management and service quality also simultaneously have a positive and significant effect on customer loyalty at Eka Walet Shop as evidenced by the f count (228,049) > f table (3.12) and has an R Square value of 0.856. The limitation of the research is the scope of the research which is only on one business and does not take into account other variables that also affect consumer loyalty.